The Performance of Purchasing Process in the System of Business Performance Evaluation - Pecinová, Zuzana; Branská, Lenka; Paták, Michal; Bojčuková, Petra (STEF92 Technology Ltd., 2017)
An important prerequisite for improving business performance is the high efficiency of internal processes, including the purchasing process. In order to increase the performance efficiency of industry enterprises as the suppliers, it is necessary to know and understand not only the course of the purchasing process in the companies of direct customers, but also their way of evaluating the performance of the suppliers, the actual purchasing process and its position in the business performance evaluation system. The article presents the results of a qualitative research carried out in the purchasing departments of two food businesses. The aim of the research was to analyze the ways of performance assessment of purchasing process in relation to business performance evaluation system. The research outcomes imply that the performance assessment system implemented by the companies has shortcomings, so there are subsequently formulated recommendations for its improvements. The article contributes to the understanding the specifics of the performance assessment in the field and provides manufacturers with information to improve their performance as suppliers in relation to the selected segment of customers.
Výkonnost nákupního procesu v systému hodnocení výkonnosti podniku
Keywords: purchasing proces; performance; performance assessment; food industry; nákupní proces; výkonnost; hodnocení výkonnosti; potravinářský průmysl